Light public–private partnerships in the water supply sector: Malawi and other case studies from sub‐Saharan Africa. (23rd October 2017) - Marson, Marta; Maggi, Elena
Abstract: The article analyzes light forms of Public–Private Partnership (PPP), namely management and service contracts, in the water supply sector of sub‐Saharan Africa, based on original research in Malawi and on a review of five additional case studies. We refer to information asymmetries and contract theory to explain the observed performances of the PPPs. The article considers the incentives to engage in the partnership and to commit effort, together with the challenges which can prevent effort from translating into actual results. The study concludes that some problems encountered by light PPP experiences are intrinsic to their incentive structure and discusses the policy implications of light PPPs promotion in the context of the Aid Effectiveness debate.